Formulasi Sediaan Serum Fraksi Aktif Ekstrak Etanol Daun Nangka (Artocarpus Heterophyllus L.) Sebagai Antioksidan - Shafi Surya Donar E K; Danang Raharjo; Kusumaningtyas Siwi Artini; Bangkit Riska Permata (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Free radicals can damage the skin and accelerate aging, so natural antioxidants are needed. Jackfruit leaves (Artocarpus heterophyllus L.) contain flavonoids that have the potential as antioxidants. This study aims to extract the active fraction from jackfruit leaves and formulate it in the form of serum. Extraction was carried out through maceration with 96% ethanol, followed by fractionation using n-hexane and ethyl acetate. Antioxidant activity was tested using the ABTS method, and the serum formulation was tested for physical stability and was accepted through irritation and hedonic tests. The results showed that the ethyl acetate fraction had the highest antioxidant activity (IC50 = 32.041 ppm). Serum with 5% active fraction showed strong activity (IC50 = 60.301 ppm), was physically stable, and was well accepted by users. Serum from the ethyl acetate fraction of jackfruit leaves has the potential as a natural skin care product with good antioxidant activity.